Conceptual design approach and ergonomics analysis of fire resistant purpose shield - Mohamed Saiful, Firdaus Hussin; Halyani, Mohd. Yassim; Nursabillilah, Mohd. Ali; Muhammad Ashraf, Fauzi; Zulkefli, Ismail; Fatin Farhana, Rosli (Asian Research Publishing Network (ARPN), 2019)
Shield was used as protection from danger centuries ago. Until this moment, there was still no shield available for firefighting purpose in safe and rescue operation. This factor has put a limit to firefighters, causing death to many victims who were in critical and dangerous situation. In this project, conceptual design will be proposed aimed to protect firefighters against fire and heat. The project was based on the existing design of Federal Reserve Unit (FRU) shield and innovated by adding the application of resisting fire. The methodology used are customer survey to fire fighters, house of quality in defining customers’ needs, morphological chart in defining concepts, Rula-analysis in measuring ergonomic score and Pugh method for selection of best design. Carbon fibre was selected as the main material for the shield because it has a very low material density of approximately 1.75 g/cm3 and very high melting point of approximately 3500 °C. In Rula-Analysis, the ergonomics final score was 3. Results show that carbon fibre is appropriate for lightweight and fireresistant shield. Ergonomics score of 3 for standing and kneeing position while holding shield is acceptable and further investigation can be recommended.